Training needs assessment for tourism businesses in Tanzania - Ladislaus Batinoluho (Bahasa Indonesia, 2022)
There is clear evidence of the skill gaps between the skills offered in training institutions and the skills required by the tourism market in Tanzania. This paper intends to assess training needs among tourism businesses in the country. The study employed a qualitative method in which Focus Group Discussions (FGDs) and Key Informant Interviews were conducted among MSMEs in the tourism industry in Tanzania. It involved a total of 117 respondents (63 females and 54 males), with the majority being tourism businesses. The study revealed that tourism businesses have varying levels of basic education, as well as specific tourism education levels. The MSMEs lack different skills and competencies, due in part to their lines of business, the levels of involvement with their business, and customer transactions. There is a need to move towards a more professional tourism business development approach and practice. This can best be achieved when a greater number of tourism MSMEs in the eight tourism sub-sectors from the five circuits work more closely together in formal location-based, cross-sub-sector circuits to gain leverage on their synergies. Also, there is a need to identify tourism skills gaps and propose mitigation measures for capacity-building training initiatives that focus on tourism business development to make Tanzania destination more competitive.